The Effect of Financial Performance, Risk, and Liquidity on Firm Value in the Manufacturing Industry Sector in Indonesia - Dian Firdaus; Eko Sudarmanto; Risna Amalia Hamzah (Sciences du Nord Economics and Business, 2024)
This study investigates the effect of financial performance, risk, and liquidity on firm value in the manufacturing sector in Indonesia. Using a sample of 60 manufacturing companies listed on the Indonesia Stock Exchange, the research employs a quantitative approach with data analyzed through SPSS version 26. Financial performance was measured by Return on Assets (ROA), risk by Debt-to-Equity Ratio, and liquidity by Current Ratio. The Price-to-Book Ratio represented firm value. The results reveal that financial performance and liquidity have a significant positive effect on firm value, while risk has a negative effect. These findings suggest that manufacturing companies in Indonesia can enhance their market value by improving profitability and liquidity while effectively managing financial risk.